Intelligent tuning of vibration mitigation process for single link manipulator using fuzzy logic - Ali, Ahmed A.; Lateef, Rana Abdul Rahman; Saeed, Mahmood Wael (Engineering science and technology, an international journal, 2017)
In this work, active vibration mitigation for smart single link manipulator is presented. Two piezoelectric transducers were utilized to act asactuator and sensor respectively. Classical Proportional (P) controller was tested numerically and experimentally. The comparison between measured results showed good agreement. The proposed work includes the introducing of fuzzy logic for tuning controller's gain within finite element method. Classical Proportional-Integral (PI), Fuzzy-P and Fuzzy-PI controllers were totally integrated as a series of [IF-Then] states and solved numerically by using Finite Element (FE) solver (ANSYS). Proposed method will pave the way on solving the tuning process totally within single FE solver with high efficiency. Proposed method satisfied mitigation in the overall free response with about 52% and 74% of the manipulator settling time when Fuzzy-P and Fuzzy-PI controllers were activated respectively. This contribution can be utilized for many other applications related to fuzzy topics.